Roles of CD3, CD4 and CD8 in synovial lymphocytes of rheumatoid arthritis - Xiong, Guangyi; Lei, Ting; Dong, Shuhui; Xu, Lina; Li, Mingshan; Wang, Ruilin (Polish Journal of Pathology, 2022)
In this study, the immunohistochemical EnVision method was applied to detect CD3, CD4 and CD8 in synovial tissues of 40 patients with rheumatoid arthritis (RA) and 10 patients with osteoarthritis (OA). In 92.5% (37/40) RA cases, lymphocytes were focally aggregated, and even germinal centers appeared, forming lymphoid follicle-like structures. The expression of CD3, CD4, and CD8 were high in synovial tissue of RA group, but low in OA group. The number of CD3, CD4+, and CD8+ lymphocytes in OA group were significantly lower than that in RA group (p < 0.05); CD4+lymphocytes in RA accounted for the majority, and mostly were focally distributed. The number of CD8+lymphocytes in the synovial tissue were small, and were mostly scattered. The number of CD4+lymphocytes were significantly higher than CD8+lymphocytes (p<0.05). Compared with the OA group, the number of CD4+T and CD8+T lymphocytes in RA group were higher, and the ratio of CD4/CD8 was higher in RA group (p < 0.05). In conclusion, the CD3, CD4 and CD8 with high level may promote the occurrence and development of RA. The ratio of CD4+/CD8+ may be used as a reference index for the diagnosis and prognosis of RA.